Understanding crystallinity indexes benchmarking concept from optimized parametric ionic liquid pretreatment using 1-ethyl-3-methylimidazolium Acetate [EMIM]Ac on oil palm biomass - Amizon Azizan; Rosmaria Abu Darim; Intan Suhada Azmi; Rafidah Jalil; Shareena Fairuz Abdul Manaf (Journal of Ionic Liquids)
So much about the crystallinity details during lignocellulosic biomass pretreatment using ionic liquid as solvent has not been highly progressively described. The high expense associated with specific ionic liquids may have impeded the advancement of their use in pretreatment and its subsequent steps. Initially, the pretreated empty fruit bunch, oil palm frond, and oil palm trunk using 1-ethyl-3-methylimidazolium acetate ([EMIM]Ac) as ionic liquid solvent during pretreatment have indicated prospective distortion of the cellulosic chains. Simply using the calculated crystallinity status, for instance, from X-Ray Diffraction or Fourier Transform Infrared Spectroscopy analyses, may assist during the early decisive point regarding pretreatment effectiveness. Thus, in this article, the crystallinity status, like the crystallinity index (CrI) from X-Ray Diffraction analysis, was used as a beneficial preliminary predictive index to describe the transformation of less ordered structures in lignocellulosic biomass as an early decisive point after pretreatment prior to any succeeding steps. For this, fifteen (15) sets of pretreatment optimization strategies with the Box-Behnken design method (Response Surface Methodology) solely on oil palm frond (OPF) were further proceeded with using [EMIM]Ac concentration percentages of 20, 40, and 60% (v/v), with OPF solid loading percentages of 5, 10, and 15% (w/v), as well as at reactor temperatures of 90, 110, and 130 °C. All the linear model terms of these independent variables, along with the 2-way interaction model between the ionic liquid and solid loading, were found to be significant to the effect of CrI on the pretreated OPF. The proposed optimized pretreatment variable region for lower CrI was observed and concluded to be approximately 48% [EMIM]Ac with a solid loading of 12% OPF-[EMIM]Ac at a temperature of 93 °C. The optimized pretreatment strategy indicated a moderate balance between ionic liquid concentration percentage and operating temperature on a solid loading per volume basis. With this optimization data route, the challenge of determining which highly efficient ionic liquid is costly during pretreatment on any biomass can be shortened by preliminary CrI value benchmarking.